Effect of ph on photocatalytic activities of biobr nanomaterials synthesized by sonochemical method - P. Patiphatpanya (2020)
© 2020, S.C. Virtual Company of Phisics S.R.L. All rights reserved. BiOBr nanomaterials were successfully synthesized in different solutions with the pH of 2–12 by sonochemical method. X-ray diffraction (XRD), scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS) results revealed the presence of pure tetragonal BiOBr nanomaterials. The photocatalytic activities of BiOBr nanomaterials were evaluated through the degradation of rhodamine B (RhB) under visible light irradiation. Clearly, the pH of precursor solution played an important role in photocatalytic activity. In this research, BiOBr flowers synthesized in a solution with the pH of 6 showed the highest photocatalytic efficiency of 99.05 % within 40 min.